Atmospheric chemistry of CF3CH2OCHF2 and CF3CHClOCHF2: Kinetics and mechanisms of reaction with Cl atoms and OH radicals and atmospheric fate of CF3C(O center dot)HOCHF2 and CF3C(O center dot)ClOCHF2 radicals - Wallington, T; Hurley, MD; Fedotov, V; Morrell, C; Hancock, G (2002)
Relative rate techniques were used to measure k(Cl + CF3CH2OCHF2) = (1.2 ± 0.1) × 10-14, k(Cl + CF3CHClOCHF2) = (5.4 ± 0.5) × 10-15, k(Cl + HC(O)OCHF2) = (2.0 ± 0.2) × 10-14, and k(Cl + CF3C(O)OCHF2) < 4 × 10-17 cm3 molecule-1 s-1 at 295 K. Cl atoms react with CF3CHClOCHF2 (isoflurane, HCFE-235da2) via H-atom abstraction to give CF3C(·)ClOCHF2 and CF3CHClOC(·)F2 radicals in yields of 92% and 8%. OH radicals react with CF3CHClOCHF2 via H-atom abstraction to give CF3C(·)ClOCHF2 and CF3CHClOC(·)F2 radicals in yields of 95% and 5%. CF3C(·)ClOCHF2 and CF3CHClOC(·)F2 add O2 to give peroxy radicals which react with NO to give the alkoxy radicals CF3C(O·)ClOCHF2 and CF3CHClOC(O·)F2. The atmospheric fate of CF3C(O·)ClOCHF2 radicals is decomposition via elimination of a Cl atom to give CF3C(O)OCHF2 and is unaffected by the method used to generate the CF3C(O·)ClOCHF2 radicals. Reaction of Cl atoms with CF3CH2OCHF2 (HFE-245fa2) proceeds via H-atom abstraction to give CF3C(·)HOCHF2 radicals in a yield which is indistinguishable from 100%. The fate of the alkoxy radical CF3C(O·)HOCHF2 is affected by the method in which it is generated. There are two competing fates for CF3C(O·)HOCHF2 radicals formed by the reaction of CF3C(OO·)HOCHF2 with other peroxy radicals; bimolecular reaction with O2 to give CF3C(O)OCHF2 and unimolecular decomposition via C-C bond scission to give a CF3 radical and HC(O)OCHF2. In contrast, decomposition is the only observable fate of CF3C(O·)HOCHF2 produced via the CF3C(OO·)HOCHF2 + NO reaction. We ascribe this observation to the formation of vibrationally excited CF3C(O·)HOCHF2 radicals in the CF3C(OO·)HOCHF2 + NO reaction. IR spectra of CF3C(O)OCHF2 and HC(O)OCHF2 are presented. The results are discussed with respect to the atmospheric chemistry of CF3CHClOCHF2 and other ethers.